(untitled) (Journal of Asian Development Studies, 2025)
This research explores the Theory of Planned Behavior (TPB) to investigate how School Health Programmes (SHP) affect behavioral change among students and drive healthy attitudes. Emphasizing that health education and awareness are key in developing healthy lifestyles and the prevention of disease, and SHPs are a vehicle to inculcate such behavior at an early age. Adopting healthy conduct requires timely awareness, and this study focuses on the potential of SHPs to transform student behavior in the long term. The study utilizes a cross-sectional empirical design with data gathered from 550 public school students of the Punjab region, both control and treatment groups, are utilized. PLS-SEM is applied to evaluate model fitness and relationships, followed by Multi-group Analysis in Smart PLS to evaluate differences across data groups. The results indicate that the treatment group exhibited significantly higher positive health behaviors than the control group, validating the use of TPB. Additionally, SHPs were found to have a significant long-term effect on behavior change. These findings highlight the importance & efficacy of long-term health programmes in education settings, especially in a developing country like Pakistan. In a practical context, the research provides a strategic model for policymakers to improve SHP design and implementation. Overall, the study stresses the need to foster healthier physical and social environments to facilitate long-term behavioral change among students and promote healthy lifestyles for better living.